بین المذاہب مکالمہ اور عالمی امن میں اسلامی کردار: The Role of Interfaith Dialogue and the Islamic Contribution to Global Peace - Shigri, farman Ali (Al-Amīr Research Journal for Islamic Studies, 2024)
In today's world, nations face numerous ideological, political, social, economic, religious, and legal challenges. The solution to these challenges lies in interfaith dialogue, which can engage various parties and encourage them to reflect more deeply on mutual issues. Such dialogue can occur between individuals, civilizations, and different religions. Islam, being a universal religion, conveys a message that transcends borders and is inherently associated with peace and security. The Prophet Muhammad employed all available means of communication to spread his message to humanity, using wisdom, insight, good counsel, and constructive debate. Throughout his life, whether during the Treaty of Hudaybiyyah, the Constitution of Medina, or in his letters to the kings of the world, the Prophet's message was one of peace. At present, the world is engulfed in wars, violence, and conflicts, with religions often clashing and even accusations of disbelief being thrown between opposing factions. To ensure lasting peace, prevent further destruction, and resolve inter-religious conflicts, interfaith dialogue becomes imperative. This paper explores the foundational principles of interfaith dialogue, its significance, the key participants, and the strategies necessary for peace-building, drawing upon Quranic verses and the teachings of the Prophet Muhammad. Ultimately, dialogue and reconciliation lead to the establishment of peace in society. Keywords: Dialogue, Religions, Islam, Peace-building, Propheticﷺ Biography